2019
DOI: 10.1021/acschemneuro.8b00340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of (R)-Modafinil and Modafinil Analogues on Dopamine Dynamics Assessed by Voltammetry and Microdialysis in the Mouse Nucleus Accumbens Shell

Abstract: Recent discoveries have improved our understanding of the physiological and pathological roles of the dopamine transporter (DAT); however, only a few drugs are clinically available for DATimplicated disorders. Among those drugs, modafinil (MOD) and its (R)enantiomer (R-MOD) have been used off-label as therapies for psychostimulant use disorders, but they have shown limited effectiveness in clinical trials. Recent preclinical studies on MOD and R-MOD have led to chemically modified structures aimed toward impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 65 publications
4
47
3
Order By: Relevance
“…In conclusion, the differential effects of (S)-CE-123 and R-modafinil in the mesocorticolimbic system are in accordance with published studies showing the behavioral and neurochemical peculiarities of analogue compounds, despite their chemical similarities to the drug from which they were derived [57]. The present study suggests that low doses of (S)-CE-123 are effective in frontal brain areas associated with cognition, with minimal effect in brain areas typically related to the rewarding properties of drugs of abuse.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In conclusion, the differential effects of (S)-CE-123 and R-modafinil in the mesocorticolimbic system are in accordance with published studies showing the behavioral and neurochemical peculiarities of analogue compounds, despite their chemical similarities to the drug from which they were derived [57]. The present study suggests that low doses of (S)-CE-123 are effective in frontal brain areas associated with cognition, with minimal effect in brain areas typically related to the rewarding properties of drugs of abuse.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to (S)-CE-123, none of the tested doses of R-modafinil stimulated dopamine transmission in the NAc shell. This observation is inconsistent with previous findings, since both Mereu et al (2017) [56] and Keighron et al (2019) [57] reported that modafinil increases dopamine levels in NAc shell. However, discrepancies between our results and previous reports might be due to differences in dose regimen, as well as in the route of administration.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…FSCV procedures follow those of recently published work from our laboratory in anesthetized mice using electrical stimulation (50). Briefly, glass sealed 100 µm carbon fiber microelectrodes were pre-calibrated with known concentrations of dopamine and changes in pH to allow for a principal component analysis (PCA) of the raw data using HDCV (UNC, Chapel Hill, NC).…”
Section: In Vivo Fast Scan Cyclic Voltammetry (Fscv)mentioning
confidence: 99%
“…The last 2-3 days of cocaine self-administration data at each dose were averaged and used to compare dose-response performance between WT and KO mice.After the completion of the above cocaine dose-response experiment, the animals were switched to cocaine self-administration under PR reinforcement schedule. During PR conditions, the work requirement (lever presses) needed to receive a cocaine infusion was raised progressively within each test session according to the following PR series:1,2,4,6,9,12,15,20,25,32,40,50, 62, 77, 95, 118, 145, 178, 219, 268, 328, 402, 492, and 603 until the break point was reached.The break point was defined as the maximal workload (i.e., number of lever presses) completed for the last cocaine infusion prior to a 1-h period during which no infusions were obtained by the animal. Animals were tested for cocaine self-administration under PR reinforcement at three doses (starting at 0.25, then 1 and then 0.5 mg/kg/infusion) from days 30 to 38.After the completion of the PR experiments, the same groups of animals continued for cocaine extinction and reinstatement tests.…”
mentioning
confidence: 99%